The genetic association of RUNX3 with ankylosing spondylitis can be explained by allele-specific effects on IRF4 recruitment that alter gene expression. Issue 8 (9th October 2015) - Vecellio, Matteo; Roberts, Amity R; Cohen, Carla J; Cortes, Adrian; Knight, Julian C; Bowness, Paul; Wordsworth, B Paul
Abstract : Objectives: To identify the functional basis for the genetic association of single nucleotide polymorphisms (SNP), upstream of the RUNX3 promoter, with ankylosing spondylitis (AS). Methods: We performed conditional analysis of genetic association data and used ENCODE data on chromatin remodelling and transcription factor (TF) binding sites to identify the primary AS-associated regulatory SNP in the RUNX3 region. The functional effects of this SNP were tested in luciferase reporter assays. Its effects on TF binding were investigated by electrophoretic mobility gel shift assays and chromatin immunoprecipitation. RUNX3 mRNA levels were compared in primary CD8+ T cells of AS risk and protective genotypes by real-time PCR. Results: The association of the RUNX3 SNP rs4648889 with AS (p<7.6×10 −14 ) was robust to conditioning on all other SNPs in this region. We identified a 2 kb putative regulatory element, upstream of RUNX3, containing rs4648889. In reporter gene constructs, the protective rs4648889 'G' allele increased luciferase activity ninefold but significantly less activity (4.3-fold) was seen with the AS risk 'A' allele (p≤0.01). The binding of Jurkat or CD8+ T-cell nuclear extracts to the risk allele was decreased and IRF4 recruitment was reduced. The AS-risk allele also affected H3K4Me1 histone methylation and associated with an allele-specific reduction in RUNX3 mRNA (p<0.05). Conclusion: We identified a regulatory region upstream of RUNX3 that is modulated by rs4648889 . The risk allele decreases TF binding (including IRF4) and reduces reporter activity and RUNX3 expression. These findings may have important implications for understanding the role of T cells and other immune cells in AS.